Examining the Prevalence of Previously Recorded Phenotypically Related Diagnoses Among Fee-for-Service Medicare Enrollees Newly Diagnosed with Mendelian Conditions - Weeks, Bill; Huynh, Grace, Stacey Y. Cao, Jeremy Smith; Bangur, Chaitanya; Weinstein, James (Journal of General Internal Medicine, 2021)
Using Vanderbilt’s patient database, Batarache et al. found that constellations of billing codes could be used to identify patients with previously unidentified Mendelian (gene-borne) diseases.1,2 Artificial intelligence-informed, billing-record-based3 physician decision support at the point of care might enable earlier diagnosis and treatment. Among the fee-for-service Medicare population, we sought to examine the prevalence with which cases of newly diagnosed Mendelian conditions had phenotypically related diagnoses in previous years